Research on bond–slip performance between pultruded glass fiber-reinforced polymer tube and nano-CaCO3 concrete - Guo Zhan; Zhu Qingxia; Wu Wenda; Chen Yu (Nanotechnology Reviews, 2020)
The article describes an experimental study on the bond–slip performance between the pultruded glass fiber-reinforced polymer (GFRP) tube and the nano-CaCO3 concrete. Taking the nano-CaCO3 concrete strength and GFRP tube thickness as primary parameters, nine specimens were designed and tested to study the influence of these parameters on the bond strength of the specimens. Besides, three specimens filled with the ordinary concrete were also tested by using the push-out tests to make comparisons with the bond performance of the specimens filled with nano-CaCO3 concrete. A total of four push-out tests were conducted on each specimen. The experimental results indicate that there are two types of axial load–slip curves for each specimen in four push-out tests. Moreover, comparison of the results of the push-out tests in the same direction shows that the bond failure load of the specimen decreases with the increase in the number of push-out tests. Based on the analysis of the test results, it is shown that the bond performance between the GFRP tube and the nano-CaCO3 concrete is better than that between the GFRP tube and the ordinary concrete. Furthermore, as the nano-CaCO3 concrete strength increases, the bond strength of the specimens decreases, indicating that the concrete strength has a negative effect on the bond strength. When the nano-CaCO3 concrete strength is relatively smaller (C20), the bond strength of the specimens decreases with the increase in the thickness of the GFRP tube. However, when the nano-CaCO3 concrete strength is relatively larger (C30 and C40), the bond strength of the specimens increases as the thickness of the GFRP tube increases.